Betsy Ross and the making of America - Miller, Marla R. (New York : Henry Holt, 2010)
A richly woven biography of the beloved patriot Betsy Ross, her fabled creation of "the first flag," and an enthralling portrait of everyday life in Revolutionary War -era Philadelphia.
Six hundred miles nearer the sun. -- The light within -- A nursery to the lord -- Pins and needles -- Crafting comfort -- The furnace of affliction. -- Combustible matters -- Domestic rebellions -- Union and disunion -- Mr. and Mrs. Ross -- Meditations in trouble -- True colors. -- Crafting colors -- Signals of independence -- The mariner's bride -- The occupied city -- Privateer to prisoner -- Peace and prosperity. -- Third time's a charm -- Lord and empire -- Brotherly love -- Fever -- The federal edifice -- Endings and beginnings. -- War, redux - - A port in the storm.
Includes bibliographical references and index.
Keywords: Ross, Betsy, -- 1752-1836.; Revolutionaries -- United States -- Biography; Flags -- United States -- History; Philadelphia (Pa.) -- History -- Revolution, 1775-1783.